In Search of Actual Border in The Shadow Lines: A Geographical and Psychological Study - Prakash Chandra Biswas; Abdullah Azad; Naimur Rahman; Rashel Mia (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This qualitative research delves into the psychological demarcations within Amitav Ghosh’s “The Shadow Lines” by an intensive study of the characters’ intricate relationships with each other, creating a sense of internationalism. Set against the backdrop of the Indian subcontinent’s partition, the novel explores the artificial divisions of caste, nation, and identity, and their profound impacts on human relationships. This study examines both primary and secondary sources to dissect the intricate relationships among the characters, highlighting the devastating effects of psychological borders compared to physical ones. While geographical demarcations physically separate people, the psychological borders ingrained in individuals’ minds create deeper, more enduring divisions. This research underscores how these mental boundaries perpetuate alienation, contrasting with the moments of collective unity despite physical separations. Through a meticulous analysis of character dynamics, the paper argues that psychological borders are more harmful, influencing emotions and identities on a fundamental level. The study offers significant insights into the themes of identity, trauma, and demarcation in literature, contributing to a deeper understanding of how mental and social divisions shape human interactions and societal structures.